Advances in Remediation of Environmental Pollutants for Sustainable Development - Rafatullah, Mohd; Siddiqui, Masoom Raza (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Environmental quality is crucial to our health, economy, lives, and for future generations. However, during the last few years, we have faced several serious challenges, which include, but are not limited to, climate change, unsustainable consumption and production, as well as various forms of pollution. These challenges are of global concerns for the sustainable development of human beings. This reprint has collected review and research papers aimed at a wide range of environmental topics: water and wastewater treatment and management, soil degradation and conservation, pollution control, the environmental impact of technologies, air quality and the indoor environment, and advanced environmental materials. Analytical methods developed for the determination of environmental pollutants were also welcomed. Papers dealing in the synthesis of adsorbents for the solid-phase extraction of environmental pollutants also fell within the scope of this Special Issue. Contributions describing novel and significant knowledge, scientific results, and advanced applications in the field of environmental sciences and technology were also welcomed. This reprint provides an integrated view of the trends in solving the problems associated with the achievement of sustainability in environmental technology.